Can bottom‐up processes of attention be a source of 'interference' in situations where top‐down control of attention is crucial?. (29th May 2017) - Nikolla, Dritan; Edgar, Graham; Catherwood, Dianne; Matthews, Tristan
Abstract : In this study, we investigate whether emotionally engaged bottom‐up processes of attention can be a source of 'interference' in situations where top‐down control of attention is necessary. Participants were asked to monitor and report on a video of a war scenario showing a developing battle in two conditions: emotionally positive and emotionally negative. Half of the participants ( n = 15) were exposed to task‐irrelevant pictures of positive emotional valence embedded within the scenario; the other half were exposed to task‐irrelevant pictures of negative emotional valence. Sensitivity and Bias scores were calculated using signal detection theory. Overall, task accuracy scores were dependent upon the valence; negative pictures had an adverse effect on performance, whereas positive pictures improved performance. We concluded that negative emotional pictures interfered with top‐down control of attention by attracting competing bottom‐up processes of attention. We found the opposite effect for positive emotional stimuli.